Influência do exercício físico aeróbico na distribuição hipocampal de neurônios imunorreativos a parvalbumina em ratos wistar: um estudo comparativo entre os sexos masculino e feminino - Placencia, Eduardo Varejao Diaz [UNIFESP] (2018)
Several studies report differences between males and females on physical exerciseinduced brain plasticity, including neurotrophic factor levels, neurogenesis, and navigation strategies in spatial memory task. However, reports in the literature show females are physically more active than males in animal models of physical exercise. With this in mind, we conducted an experimental study to investigate the effect of sex on the brain of rats submitted to same volume and intensity of aerobic exercise. To do so, we evaluated the hippocampal distribution of parvalbumin-containing neurons in male and female rats submitted to 4 weeks of aerobic exercise on a treadmill at 12 m/min, 30 min per day. Parvalbumin is an important calcium binding protein present in gabaergic neurons, furthermore, it has been used as a neuromarker in several studies. Our results show that, in both sexes, physical exercise increased hippocampal density of parvalbumin neurons in the cornus amm onis (CA1, CA2/CA3) and hilus subfields. No difference in exercise-induced hipocampal parvalbumin density was found between male and female rats. These findings suggest that aerobic exercise promotes similar effects on hippocampal distribution of parvalbumin neurons of male and female rats, especially when they are submitted to the same volume and intensity of physical exercise.